Computer vision and applications: a guide for students and practitioners - Jähne, Bernd; Haußecker, Horst (Academic Press, 2000)
Sensors and imaging -- Signal processing and pattern recognition -- Application gallery
Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books; Maschinelles Sehen